A feedback loop links brownification and anoxia in a temperate, shallow lake. (20th July 2014) - Brothers, S.; Köhler, J.; Attermeyer, K.; Grossart, H. P.; Mehner, T.; Meyer, N.; Scharnweber, K.; Hilt, S.
Abstract : This study examines a natural, rapid, fivefold increase in dissolved organic carbon (DOC) concentrations in a temperate shallow lake, describing the processes by which increased DOC resulted in anoxic conditions and altered existing carbon cycling pathways. High precipitation for two consecutive years led to rising water levels and the flooding of adjacent degraded peatlands. Leaching from the flooded soils provided an initial increase in DOC concentrations (from a 2010 mean of 12 ± 1 mg L −1 to a maximum concentration of 53 mg L −1 by June 2012). Increasing water levels, DOC, and phytoplankton concentrations reduced light reaching the sediment surface, eliminating most benthic primary production and promoting anoxia in the hypolimnion. From January to June 2012 there was a sudden increase in total phosphorus (from 57 µg L −1 to 216 µg L −1 ), DOC (from 24.6 mg L −1 to 53 mg L −1 ), and iron (from 0.12 mg L −1 to 1.07 mg L −1 ) concentrations, without any further large fluxes in water levels. We suggest that anoxic conditions at the sediment surface and flooded soils produced a dramatic release of these chemicals that exacerbated brownification and eutrophication, creating anoxic conditions that persisted roughly 6 months below a water depth of 1 m and extended periodically to the water surface. This brownification‐anoxia feedback loop resulted in a near‐complete loss of macroinvertebrate and fish populations, and increased surface carbon dioxide (CO2 ) emissions by an order of magnitude relative to previous years.